Come back or stay? - Spend here or there?: Temporary versus permanent migration and remittance patterns in the Republic of Moldova - Pia R. Pinger (Kiel Institute for the World Economy (IfW), 2007)
This paper examines the determinants of temporary and permanent migration and the impact of the return decision on remittances patterns. Using a new detailed household dataset on migration in the Republic of Moldova, it is shown that return is determined by the economic conditions at home and abroad as well as by the legal status in the host country. Especially economic frustration turns out to be an important push factor for permanent migration. Besides, family ties play an important role, as do respective migrant networks. Concerning remittances, the results indicate that temporary migrants remit around 30% more than their permanent counterparts even though they often reside in lower wage countries. Overall, the findings indicate that temporary migration is relatively more favorable for developing countries as it fosters higher remittances, repatriation of skills and home savings.
Keywords: F22; F24; O15; 330; permanent migration; temporary migration; remittances; economic development; Rücküberweisung (Migranten); Migranten; Haushaltsökonomik; Rückwanderung; Moldawien